Method for preparing high-purity nano silicon dioxide from organic silicon waste contact

Through the steps of acid leaching, solid-liquid separation and titration reaction, the nano-scale silicon dioxide preparation process of organic silicon waste contacts is simplified, and the problems of complex processes and high energy consumption in the existing technology are solved, and the preparation of high-purity nano-scale silicon dioxide and effective silicon recovery are realized.

CN120081383AActive Publication Date: 2025-06-03XINJIANG INST OF ECOLOGY & GEOGRAPHY CHINESE ACAD OF SCI +1

Patent Information

Application Number
CN202510271060.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-07
Publication Date
2025-06-03
Estimated Expiration
2045-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively recover nanoscale silica in silicone waste contacts, and the process is complex, the energy consumption is high, and the product particle size is unevenly dispersed.

Method used

Through steps such as acid leaching, suction filtration, solid-liquid sodium hydroxide separation, titration reaction and drying and calcining, the process flow is simplified to prepare nano-scale silica with uniform particle size dispersion.

Benefits of technology

The preparation of high-purity nanoscale silicon dioxide is realized, the process flow is simplified, energy consumption and cost are reduced, and the recovery rate of silicon and the added value of the market are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120081383A_ABST
    Figure CN120081383A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing nano silicon dioxide from an organic silicon waste contact body, which is used for reducing the landfill volume and the harm of hazardous wastes to the environment. The method comprises the following steps: carrying out proper pretreatment on the organic silicon waste contact, carrying out acid leaching and impurity removal by using HCl, and then directly reacting NaOH with residues to prepare Na2SiO3. In the preparation process, Na2SiO3 is used as a silicon source, NH4Cl is used as a precipitator, and the catalytic hydroxyl self-condensation of Na2SiO3 is carried out in a polyalcohol / micromolecule alcohol / polyquaternium / hydrosolvent system. The influence of the proportion of the polyalcohol, the ethanol and the polyquaternium on the particle size, the dispersity and the shape of the amorphous SiO2 nanoparticles is investigated. And finally, the silicon-containing solid waste is prepared into the spherical amorphous SiO2 nano-particles with good dispersion, the yield and the purity are high, the particle size is about 100 nm, and the particle size dispersion is uniform.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hazardous waste resource recycling and environmental protection, and relates to a method for preparing nano-silica from silicone waste catalyst. Background Art

[0002] The most important and complex part in production is the synthesis of methylchlorosilane monomers. Among them, the direct method is widely used because of its simple process, high yield, no solvent, low danger, and easy realization of continuous large-scale production. This method uses ternary copper as a catalyst, which is mixed with silicon powder to form an active catalytic contact body, playing an important role in improving the selectivity and yield of methylchlorosilane. During continuous reactions, reasons such as impurity accumulation and catalyst deactivation will significantly reduce the conversion rate of silicon powder and the selectivity of dimethylchlorosilane (M 2 ). The industrial waste residue formed by discharging unreacted silicon powder and deactivated catalyst from the reactor to maintain production stability is called silicone waste catalyst.

[0004] In the past, landfilling was commonly used to treat silicone waste catalyst. This method not only causes great pollution to the environment but also wastes a large amount of valuable resources such as silicon and copper. In recent years, the research work on waste catalyst resource utilization has mainly focused on forming metal salt solutions through chemical treatment and then preparing various metals and their derivatives through chemical reduction, electrolysis, etc. The residues are obtained as silicon powder after chemical and physical impurity removal. In this process, the separation conditions will greatly affect the solid-liquid separation effect, and the process is relatively complex, prone to generating new wastes, increasing the treatment burden and energy consumption. At the same time, the solid-liquid separation process also affects the utilization rate and performance of recycled substances such as silicon. In the prior art, the resource recovery and utilization of silicone waste catalyst mainly focus on the recovery of copper resources, and most of the reports on silicon resources are methods for recovering silicon powder.

[0005] CN117416963A discloses a method for preparing silicon powder from silicone waste catalyst, including the following steps: (1) performing copper removal treatment on the silicone waste catalyst to obtain copper-removed residue of the silicone waste catalyst; (2) mixing the copper-removed residue of the silicone waste catalyst with water to form a slurry; (3) performing two-stage magnetic separation on the slurry to obtain a silicon-rich non-magnetic product; (4) roasting, pickling, and drying the silicon-rich non-magnetic product to obtain silicon powder.

[0006] CN115181998A discloses a method for recovering silicon powder from silicone waste contact bodies, comprising the following steps: Oxidative acid leaching: adding the silicone waste contact bodies, sulfuric acid solution A and an adjusting agent into an air flotation mechanical stirring coupled leaching tank, introducing air into the air flotation mechanical stirring coupled leaching tank and continuously operating a slag scraper to scrape off the surface air flotation layer, and performing mechanical stirring for oxidative leaching to obtain a leaching slurry; Solid-liquid separation: subjecting the leaching slurry to solid-liquid separation to obtain a copper-containing leaching solution and leaching residues, and washing, pressure filtering and neutralizing the leaching residues to obtain silicon powder.

[0007] CN115058586A discloses a method for recovering silicon powder from silicone waste contact bodies, comprising the following steps: subjecting the silicone waste contact bodies to ball milling and pulping treatment to obtain a pulping liquid, then performing magnetic separation to remove iron from the pulping liquid, and pressure filtering to obtain iron-removed copper-containing waste silicon powder; adding the iron-removed copper-containing waste silicon powder and sulfuric acid solution into a flotation machine and adjusting the pulp to form a mixed pulp, then allowing the flotation machine to inhale air and continuously operating a scraper device to scrape off the surface air flotation layer, and performing mechanical stirring for oxidative leaching, and after the leaching is completed, performing solid-liquid separation to obtain leaching residues and a copper-containing leaching solution; subjecting the leaching residues to a washing and pressure filtering process to obtain a washing filtrate and silicon powder.

[0008] The above-mentioned prior art for recovering silicon powder from silicone waste contact bodies has low economic value. Through retrieval, there are few reports on preparing nano-scale silica using silicone waste contact bodies as raw materials. Summary of the Invention

[0009] In order to overcome the defect that it is difficult to prepare nano-scale silica from silicone waste contact bodies, after separating the impurities in the silicone waste contact bodies, the present invention does not add oxidants such as hydrogen peroxide. Only through acid leaching, suction filtration, solid-liquid separation with sodium hydroxide, titration reaction and suction filtration again, and finally drying the gel and calcining to remove volatile impurities, nano-scale silica with uniform particle size distribution is obtained, simplifying the recovery process, reducing the amount of waste generated, reducing the impact on the recovered substances, energy consumption and cost during the recovery process, improving the effective recovery and market added value of silicon in the silicone waste contact bodies, and alleviating the environmental pressure. The present invention realizes the above object through the following technical solutions:

[0010] A method for preparing nano-scale silica from silicone waste contact bodies, comprising the following steps:

[0011] S1. Roasting the silicone waste contact bodies under a mixed gas of oxygen and nitrogen to obtain a roasted waste contact body material;

[0012] S2. Mixing the roasted waste contact body material with concentrated hydrochloric acid, continuously stirring under heating and ultrasonic conditions to obtain an acid leaching slurry, washing and suction filtering multiple times until the filtrate is neutral to obtain filter residues;

[0013] The filter residues obtained from S3 and S2 are mixed evenly with sodium hydroxide and sodium fluoride, then evenly mixed with water, heated and stirred for reaction, and filtered to obtain a sodium silicate solution;

[0014] S4: Polyhydric alcohol, a C1-3 monohydric alcohol, and poly(dimethyldiallylammonium chloride) are added to the sodium silicate solution to obtain solution A. An ammonium chloride solution is slowly added to solution A, and the amount of the ammonium chloride solution is adjusted to make the pH of the mixed solution 6-7, obtaining a gel-like substance;

[0015] S5: After the gel-like substance is left standing for aging, it is washed, suction-filtered, dried, calcined, and ground to obtain nanoscale silicon dioxide.

[0016] Preferably, in step S1, the volume percentage of oxygen in the mixed gas is 5-20%, the roasting temperature is 600-1000 °C, and the roasting time is 30-90 min.

[0017] Preferably, in step S2, the concentration of hydrochloric acid is 6-12 mol·L -1 , preferably 10-12 mol·L -1 , the acid leaching time is 60-180 min, the heating temperature is 40-60 °C, the ultrasonic power is 100-300 W, and the ultrasonic frequency is 60-180 kHz; the solid-liquid ratio of the roasted waste catalyst body to the hydrochloric acid solution is 1-2 kg:1 L. Under ultrasonic and heating conditions, the roasted waste catalyst body is fully leached with concentrated hydrochloric acid, which can effectively remove impurities and increase the silicon content.

[0018] Preferably, in step S3, the mass ratio of the filter residue, sodium hydroxide, and sodium fluoride is 1:5-6:0.005-0.01. The amount of sodium hydroxide is in excess to ensure that silicon reacts fully. The inventor also found that adding a small amount of fluoride ions to the system is beneficial to promoting the reaction and increasing the yield of sodium silicate.

[0019] Preferably, in step S3, there is no special limitation on the amount of water added. For example, the amount of water is 10-20 times the mass of the filter residue, such as 15 times; the reaction under heating and stirring is carried out at 70-95 °C for 1-3 h. Filtration is performed using a 0.3-0.5 μm ultra-fine filter membrane.

[0020] Preferably, in step S4, the polyhydric alcohol is selected from at least one of polyethylene glycol and polypropylene glycol, and the number-average molecular weight of the polyhydric alcohol is 400-800; the C1-3 monohydric alcohol is selected from at least one of methanol, ethanol, and isopropanol; the number-average molecular weight of poly(dimethyldiallylammonium chloride) is 40000-60000.

[0021] The inventor unexpectedly found that when performing the titration reaction of ammonium chloride with sodium silicate, in the system, the presence of a certain amount of polyhydric alcohol, C1-3 monohydric alcohol, and quaternary ammonium salt cationic surfactant can reduce the particle size of the obtained nano-sized silica to below 80 nm, and the particle size of the obtained nano-sized silica is evenly dispersed. However, it is necessary to reasonably control the relative dosages of the polyhydric alcohol, C1-3 monohydric alcohol, and quaternary ammonium salt cationic surfactant, the chain length (i.e., molecular weight) of the polyhydric alcohol, and the concentration of sodium silicate.

[0022] Preferably, in step S4, in solution A, the concentration of the polyhydric alcohol is 3-5 wt%, the concentration of the C1-3 monohydric alcohol is 30-40 wt%, the concentration of poly(dimethyldiallylammonium chloride) is 0.2-0.3 wt%, the concentration of sodium silicate is 0.4-1.0 mol / L, preferably 0.4-0.6 mol / L. The ammonium chloride solution is slowly added to solution A by adding the ammonium chloride solution to solution A through a peristaltic pump, and the concentration of the ammonium chloride solution is 1-2 mol / L. Relative to the dosage of the polyhydric alcohol and the C1-3 monohydric alcohol, it is necessary to strictly control the molecular weight and dosage of poly(dimethyldiallylammonium chloride), otherwise, the effect of small particle size and uniform particle size dispersion cannot be achieved.

[0023] Preferably, in step S5, the standing time is 12-24 h, the washing is carried out by multiple suction filtration washes with deionized water, dried to a constant weight, and calcined at 600-700 °C for 5-10 h.

[0024] Advantages of the present invention:

[0025] First, the present invention only prepares high-purity nano-sized silica by acid-base treatment of the calcined material of the organic silicon waste contact body, which simplifies the process flow, improves the recovery rate, reduces the impact on the recovered material during the separation process, as well as energy consumption and cost, and reduces the waste generated during the recovery process. At the same time, no oxidants such as hydrogen peroxide are added, which can reduce the requirements for the corrosion resistance of equipment and facilitate industrial promotion.

[0026] Second, adopting the preparation process of the present invention, especially when performing the titration of ammonium chloride with sodium silicate in step S4, by adding a combination of polyhydric alcohol, C1-3 monohydric alcohol, and high-molecular polyquaternary ammonium salt, the average particle size of the obtained nano-sized silica is less than 100 nm, and the particle size dispersion is good, with a span value below 0.5.

[0027] Third, the preparation method of the present invention is stable, effectively recovers silicon in the organic silicon waste contact body, and improves the market added value of the product. Description of the drawings

[0028] Figure 1 is the XRD pattern of the nano-sized silica powder obtained in Example 1 and PDF#01-082-1555.

[0029] Figure 2 It is the SEM image of the nano-scale silica powder obtained in Example 1.

[0030] Figure 3 It is the FTIR image of the nano-scale silica powder obtained in Example 1. Detailed implementation manners

[0031] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention.

[0032] The silicone waste catalyst samples used in the embodiments of the present invention are from Xinjiang industrial silicon enterprises and have undergone Cu recovery. Because they contain carbon, they are first calcined in a muffle furnace at 1000 °C for 6 hours, and then ground with a planetary ball mill and sieved through a 200-mesh sieve. The sieved silicone waste catalyst is detected and analyzed by an Agilent 5900 type inductively coupled plasma emission spectrometer and a German Bruker TigerII type X-ray fluorescence spectrometer. Its chemical composition is shown in Table 1. Except for Ag, all substances are expressed in the form of oxides. Actually, in the silicone waste catalyst, most of the silicon exists in the form of elemental silicon.

[0033] Table 1 Chemical composition of silicone waste catalyst

[0034] Composition <![CDATA[SiO 2 > <![CDATA[Fe 2 O 3 > <![CDATA[Al 2 O 3 > CaO <![CDATA[SO 3 > <![CDATA[TiO 2 > Ag <![CDATA[Sodium 2 O]]> <![CDATA[P 2 O 5 > CuO Content (%) 89.000 3.683 2.570 2.375 1.360 0.416 0.219 0.060 0.053 0.051

[0035] Example 1

[0036] S1. Under a mixed gas of oxygen and nitrogen (the volume ratio of oxygen to nitrogen is 1:9), place the silicone waste catalyst in a resistance furnace and calcine it at 600 °C for 75 min to obtain a calcined waste catalyst material;

[0037] S2. Prepare 1 L of 12.0 mol·L -1 hydrochloric acid solution, mix it with 1 kg of the calcined waste catalyst material, heat it to 50 °C, and continuously stir it at a speed of 120 rpm under ultrasonic conditions of 200 W and 80 kHz for 120 min to obtain an acid-leaching slurry; repeatedly rinse the acid-leaching slurry with a circulating water vacuum pump for multiple times until the pH of the washing liquid is neutral, and then filter it to obtain a leached residue;

[0038] S3. Charge the residue, sodium hydroxide, and sodium fluoride in a mass ratio of 1:5:0.01, mix them evenly, add 15 times the mass of water of the residue, heat it to 90 °C, and maintain stirring and reaction at 90 °C for 100 min to obtain a sodium silicate solution, and filter it through a 0.45-μm membrane to obtain a sodium silicate filtrate;

[0039] S4. Add PEG400, methanol, and polydimethyldiallylammonium chloride (molecular weight 40,000) to the sodium silicate filtrate, and dilute with water to obtain Solution A. The concentration of sodium silicate in Solution A is 0.4 mol / L, the concentration of PEG600 is 3 wt%, the concentration of ethanol is 40 wt%, and the concentration of polydimethyldiallylammonium chloride is 0.2 wt%. Under stirring conditions, add a 2.0 mol / L ammonium chloride solution to Solution A through a peristaltic pump. Monitor the pH in real time during the dropping process. When the pH of the system reaches 7, stop adding ammonium chloride to obtain a gel-like substance;

[0040] S5. Let the gel-like substance stand for aging for 24 h, wash it repeatedly through a circulating water vacuum pump, filter it by suction, then dry it in an electrothermal blast drying oven at 105 °C. The dried product is ground, and then calcined in a muffle furnace at 600 °C for 4 hours, and ground using a planetary ball mill to obtain nano-scale silica powder with a purity of 98.72% and a yield of 96.13%. The purity is tested with an X-ray fluorescence spectrometer, and the yield y is calculated according to the following formula: Let the mass of silicon in the waste silicone catalyst that can theoretically be converted into SiO 2 be m1, and the mass of the finally obtained nano-scale silica powder product be m2.

[0041]

[0042] Use a Bruker Tiger II X-ray fluorescence spectrometer in Germany to determine the composition of the nano-scale silica powder. The results are shown in Table 2 below:

[0043] Table 2 XRF analysis of the nano-silica sample prepared by acid leaching with 12 mol·L -1 hydrochloric acid

[0044]

[0045] If 6 mol·L -1 hydrochloric acid is used for acid leaching in Step S2, then in the finally obtained nano-scale silica, the content of SiO 2 is 96.04%. If the acid leaching in Step S2 is not carried out, the content of SiO 2 in the finally obtained product is 91.72%. Therefore, the acid leaching step can significantly improve the product purity, and 10 - 12 mol·L -1 hydrochloric acid is appropriate.

[0046] Figure 1 is the XRD pattern of the nano-scale silica powder obtained in Example 1 and the standard PDF card #01 - 082 - 1555 of amorphous SiO 2 . A large, wide, and flat peak is observed at 2θ = 23°. Therefore, this sample is considered to be amorphous nano-silica.

[0047] Figure 2 It is the SEM image of the nanoscale silica powder obtained in Example 1.

[0048] Figure 3 It is the FTIR image of the nanoscale silica powder obtained in Example 1. There is a relatively wide absorption band at 3471 cm -1 and a sharp absorption band at 1635 cm -1 , which is attributed to the O-H bond in the SiO 2 precursor particles. Strong absorption bands are observed at 802 cm -1 and 462 cm -1 . These absorption peaks indicate the formation of the Si-O-Si bond, which is characteristic of the silica material. The peak at 1091 cm -1 indicates the formation of the asymmetric vibration of Si-O-Si. Therefore, the FTIR spectrum indicates the formation of the nanoscale silica material, and the FTIR analysis supports the XRD results.

[0049] Example 2

[0050] Other conditions are the same as those in Example 1, except that in step S3, the filter residue, sodium hydroxide, and sodium fluoride are fed in a mass ratio of 1:6:0.005.

[0051] Example 3

[0052] Other conditions are the same as those in Example 1, except that in step S4, PEG400 is replaced by PEG800, and the concentration of PEG800 in solution A is 5 wt%; the ethanol concentration is 30 wt%.

[0053] Example 4

[0054] Other conditions are the same as those in Example 1, except that in step S4, the molecular weight of polydimethyldiallylammonium chloride is 60000, and the concentration of polydimethyldiallylammonium chloride in solution A is 0.3 wt%.

[0055] Example 5

[0056] Other conditions are the same as those in Example 1, except that in step S4, the concentration of polydimethyldiallylammonium chloride in solution A is 0.1 wt%.

[0057] Example 6

[0058] Other conditions are the same as those in Example 1, except that in step S4, the concentration of polydimethyldiallylammonium chloride in solution A is 0.4 wt%.

[0059] Comparative Example 1

[0060] Other conditions are the same as in Example 1, except that in step S3, sodium fluoride is not added.

[0061] Comparative Example 2

[0062] Other conditions are the same as in Example 1, except that in step S4, PEG400 is not added.

[0063] Comparative Example 3

[0064] Other conditions are the same as in Example 1, except that in step S4, ethanol is not added.

[0065] Comparative Example 4

[0066] Other conditions are the same as in Example 1, except that in step S4, polydimethyldiallylammonium chloride is not added.

[0067] Comparative Example 5

[0068] Other conditions are the same as in Example 1, except that in step S4, a 1.0 mol / L sulfuric acid solution is added to solution A through a peristaltic pump.

[0069] The indexes of the nano-silica products obtained from the above examples and comparative examples are listed in Table 3 below.

[0070] Table 3 Indexes of Nano-carbon Dioxide Products

[0071]

[0072]

[0073] Span represents the particle size dispersity of the particles. The smaller the span value, the narrower the particle size distribution. The span value is calculated according to the following formula:

[0074] A large amount of silicon-containing waste generated by various silicon production enterprises has the potential to produce nano-silica. First, the organosilicon waste contact body is calcined and then subjected to ultrasonic acid leaching with 12 mol / L hydrochloric acid, and the purity of SiO 2 is increased, and the yield can reach more than 94%. Using NH 4 Cl as a precipitant, polyethylene glycol, small molecule alcohols, and polyquaternary ammonium salts are added for modification, and nano-silica particles with a particle size of around 100 nm, a spherical shape, good dispersibility, and an amorphous structure are successfully prepared. The method of the present invention can effectively reduce the waste of resources and the cost generated by landfilling, and can also avoid environmental pollution caused by landfilling.

Claims

1. A method for preparing nano-silicon dioxide from waste organic silicon contacts, characterized in that: The following steps are involved: S1. roasting the waste organosilicon contacts in a mixed gas of oxygen and nitrogen to obtain a waste contact roasting material; S2, the spent contact body roasting material is mixed with concentrated hydrochloric acid, heated and continuously stirred under ultrasonic conditions to obtain an acid leaching slurry, which is washed and filtered multiple times until the filtrate is neutral to obtain a filter residue; The filter residue obtained in S3 and S2 is mixed evenly with sodium hydroxide and sodium fluoride, water is added to mix evenly, heated and stirred to react, and filtered to obtain a sodium silicate solution; S4, adding polyol, C1-3 monohydric alcohol, and polydimethyldiallylammonium chloride to the sodium silicate solution to obtain solution A, slowly adding the ammonium chloride solution to solution A, adjusting the amount of the ammonium chloride solution to make the pH of the mixed solution 6-7, and obtaining a gel-like substance; S5. After the gel-like substance is allowed to stand for aging, it is washed, filtered, dried, calcined, and ground to obtain nano-scale silicon dioxide.

2. The method according to claim 1, characterized in that In step S1, the volume proportion of oxygen in the mixed gas is 5-20%, the roasting temperature is 600-1000° C., and the roasting time is 30-90 min.

3. The method according to claim 1, characterized in that In step S2, the concentration of hydrochloric acid is 6 to 12 mol·L -1 , preferably 10 to 12 mol·L -1 The acid leaching time is 60-180 minutes, the heating temperature is 40-60°C, the ultrasonic power is 100-300W, and the ultrasonic frequency is 60-180kHz; the solid-liquid ratio of the waste contact body roasting material to the hydrochloric acid solution is 1-2kg:1L.

4. The method according to claim 1, characterized in that: In step S3, the mass ratio of the filter residue, sodium hydroxide and sodium fluoride is 1:5-6:0.005-0.

01.

5. The method according to claim 1, characterized in that In step S3, the amount of water added is 10-20 times the mass of the filter residue; the heating and stirring reaction is carried out at 70-95° C. for 1-3 hours; and the filtration is carried out using a 0.3-0.5 μm ultrafine filter membrane.

6. The method according to claim 1, characterized in that In step S4, the polyol is selected from at least one of polyethylene glycol and polypropylene glycol, and the number average molecular weight of the polyol is 400-800; the C1-3 monohydric alcohol is selected from at least one of methanol, ethanol, and isopropanol; and the number average molecular weight of polydimethyldiallylammonium chloride is 40000-60000.

7. The method according to claim 1, characterized in that In step S4, in solution A, the concentration of the polyol is 3-5wt%, the concentration of the C1-3 monohydric alcohol is 30-40wt%, the concentration of the polydimethyldiallylammonium chloride is 0.2-0.3wt%, and the concentration of the sodium silicate is 0.4-1.0mol / L.

8. The method according to claim 7, characterized in that In solution A, the sodium silicate is 0.4-0.6 mol / L.

9. The method according to claim 1, characterized in that: In step S5, the standing time is 12-24 hours, the washing is performed by multiple suction filtration with deionized water, the product is dried to a constant weight, and calcined at 600-700° C. for 5-10 hours.

Citation Information

Patent Citations

  • Hydrophobically associating dimethyl diallyl ammonium chloride cation flocculating agent and preparation method thereof

    CN104163887A

  • Preparation method of high-purity precipitated and hydrated silica

    CN107176611A

  • Preparation method of light silicon dioxide nano-microspheres

    CN107176612A

  • Method for preparing silicon powder from organic silicon waste contact

    CN117416963A

  • Prepn. of finely divided silica from alkali-silicate soln. - by neutralisation with acid and treatment with poly-di:methyl-di:allyl-ammonium salts

    DE4042144A1

Cited By

  • Method for producing nanosilica using organosilicon waste catalysts

    JP7850405B1